Congenital Venous Malformation in an 8-year-old Female Child treated with Ethanol Injection - Thakkar, Umang G.; Raval, Manish N.; Vanikar, Aruna V. (Puerto Rico Health Sciences Journal, 2017)
Venous malformations (VMs) are the most frequent slow-flow vascular malformations referred to specialized centers. They can also threaten life because of bleeding, expansion or obstruction of vital structures. MRI imaging is the gold standard for pretherapeutic evaluation of VMs. To diminish the volume of the malformation, percutaneous sclerotherapy is the standard treatment. The aim is to obliterate the channels by causing damage to the endothelium with subsequent inflammation and fibrosis. We report our experience with use of ethanol for VMs ablation in an 8 years old female child.